Influence of the Aggregate Shape and Resistance to Fragmentation on Unbound Base Layer Resilient Modulus - Vilius Filotenkovas; Audrius Vaitkus (The Baltic Journal of Road and Bridge Engineering)
The performance of unbound base materials, exclusively of the upper base layers, besides compaction level and layer thickness, depends on unbound material type, aggregates shape, fine content and mechanical properties of aggregates. The response of the pavement structure to loading is expressed through stress and strain magnitudes, accumulation of which leads to layer permanent deformations. One of the key factors for designing unbound base layers is resilient modulus, which can be found from triaxial tests. The aim of the research is to analyse the effect of the aggregate particle shape, structure and the resistance to crushing properties on resilient modulus of the upper layers of the unbound base layers. The following properties have been determined during the tests: aggregate particle size distribution, particle shape and flakiness, percentage of crushed and broken particle surfaces, density, water absorption, resilient modulus under low stress level loading. According to the performed research with tested aggregate mixtures, it is assumed that most influence on resilient modulus is exerted by aggregate whole granular size distribution, water absorption and the largest aggregate particle surface angularity. Resilient modulus in the tested dolomite fraction mixtures differing from 32 mm to 56 mm showed any reasonable difference with mean nominal pressures being higher than 300 kPa.